2009
DOI: 10.1063/1.3224203
|View full text |Cite
|
Sign up to set email alerts
|

Erbium-doped GaN optical amplifiers operating at 1.54 μm

Abstract: Strip optical waveguides based on erbium ͑Er͒-doped AlGaN/GaN:Er/AlGaN heterostructures have been fabricated and characterized in the optical communication wavelength window near 1.54 m. The propagation loss of these waveguide amplifiers have been measured at 1.54 m and found to be 3.5 cm −1. Moreover, the optical amplification properties of the waveguides were measured using a signal input at 1.54 m and a broadband GaN light-emitting diode at 365 nm as pump source. A relative signal enhancement of ϳ8 cm −1 wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
33
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 46 publications
(33 citation statements)
references
References 15 publications
0
33
0
Order By: Relevance
“…We have also assumed the attenuation of the waveguide of 1.5 dB/mm. 10 With 50 mW pump power, the theoretical power spectral density emitted from the waveguide is Ϫ55 dBm/2 nm, which is about 1 dB higher than the measured value. This reduced efficiency is attributed to the nonradiative recombination and Auger recombination for the transition from the metastable level ͑ 4 I 13/2 ͒ to the ground level ͑ 4 I 15/2 ͒.…”
Section: ͑1͒mentioning
confidence: 83%
See 2 more Smart Citations
“…We have also assumed the attenuation of the waveguide of 1.5 dB/mm. 10 With 50 mW pump power, the theoretical power spectral density emitted from the waveguide is Ϫ55 dBm/2 nm, which is about 1 dB higher than the measured value. This reduced efficiency is attributed to the nonradiative recombination and Auger recombination for the transition from the metastable level ͑ 4 I 13/2 ͒ to the ground level ͑ 4 I 15/2 ͒.…”
Section: ͑1͒mentioning
confidence: 83%
“…Optical amplification in Er-doped GaN waveguide has also been demonstrated using a 365 nm light emitting diode optical pumping source. 10 UV pumping above the GaN bandgap excited free electrons and holes and subsequently the electrons and holes transfer their energy to the doped erbium ions and produce sufficient carrier population on the 4 I 13/2 band which is responsible for emission in the 1550 nm wavelength window. This above bandgap excitation was demonstrated to be more efficient than below bandgap excitation.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…These materials are of great importance for integrated optical devices. [1,2] In terms of material science, as an alternative to the erbium-doped fiber amplifiers. the incorporation of the magnified function in an integrated optical circuit, which is designed for routing and switching optical signals, [3,4] requires the development of materials which exhibit high amplification efficiencies.…”
Section: Introductionmentioning
confidence: 99%
“…Dahal et al [58] demonstrated a strip of optical waveguides based on Er-doped AlGaN/GaN:Er/AlGaN heterostructures, which were characterized in the optical communication wavelength window near 1.54 μm. The propagation loss of this waveguide amplifier at 1.54 μm was 3.5 cm À1 , and a relative signal enhancement of 8 cm À1 was observed.…”
Section: Propagation Guiding and Localization Of Resonance Modesmentioning
confidence: 99%